2000
DOI: 10.1038/modpathol.3880111
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 7 and 20 Expression in Choroid Plexus Tumors: Utility in Differentiating These Neoplasms from Metastatic Carcinomas

Abstract: Choroid plexus tumors are relatively rare lesions, accounting for fewer than 1% of intracranial neoplasms (1, 2). They may exhibit a wide spectrum of histologic patterns, including acinar (3, 4), mucussecreting (5, 6), oncocytic (7,8), pigmented (9, 10), tubular (11), and metaplastic (5, 12, 13) variants. Distinguishing these tumors from metastatic carcinomas, a matter of considerable therapeutic and prognostic significance, therefore can be problematic. A number of potential immunohistochemical markers for ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Cytokeratins have been reported to be effective in distinguishing between various subsets of primary and metastatic carcinomas in different anatomical sites. More specifically, many authors have studied the coordinate expression of CK7 and CK20 and reported the high sensibility and specificity of their association [6][7][8][9][10][11][12][13]. In our study we found that when these markers are both positive, both negative or when CK7 is positive and CK20 is negative there is relative success in finding possible origins in finding possible origins for bone metastasis from carcinoma.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Cytokeratins have been reported to be effective in distinguishing between various subsets of primary and metastatic carcinomas in different anatomical sites. More specifically, many authors have studied the coordinate expression of CK7 and CK20 and reported the high sensibility and specificity of their association [6][7][8][9][10][11][12][13]. In our study we found that when these markers are both positive, both negative or when CK7 is positive and CK20 is negative there is relative success in finding possible origins in finding possible origins for bone metastasis from carcinoma.…”
Section: Discussionsupporting
confidence: 58%
“…A panel of tissue-or organ-specific markers is typically used. Thus, many authors underline the important role that cytokeratines and other specific markers play in the discrimination of primary tumor lineage and determination of metastatic disease [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…28 If true, then findings from the present study suggest that, in dogs, ependymal differentiation occurs in a large proportion of both CPPs and CPCs, but its appearance is not correlated with histological grade as has been suggested for human CPTs. 17,32 Wide spectrum cytokeratin and CAM5.2 were expressed by an unexpectedly low number of both NCP and CPTs indicating that neither is an optimal marker of CPTs. Results of the current study are in contrast to most other studies, in which cytokeratin is expressed by both normal and neoplastic choroid plexus epithelium.…”
Section: 33mentioning
confidence: 99%
“…5 In particular, the differential expression profile of various cytokeratin (CK) types by tumors at different primary locations can be essential in determining the origin of a malignant tumor. 1,2,4,[6][7][8] CKs are intermediate filament proteins and 20 subtypes have been classified based on isoelectric pH (focusing) and molecular weight. 5,[9][10][11] Two of the most used stains are CK20 and CK7.…”
mentioning
confidence: 99%